Antiretroviral Treatment and Resistance Patterns in HIV-Infected Children (2015)
Paediatric HIV-infected patients have higher risk of developing resistance to antiretroviral drugs, and from public health perspective, drug resistance remains a limiting factor for effective management of HIV infection in children. We reviewed the current evidences available on the antiretroviral treatment and resistance patterns in HIV-infected children. Prevalence of HIV drug resistance varied among the three main classes of antiretroviral drugs, namely nucleoside reverse transcriptase inhibitors, non-nucleoside reverse transcriptase inhibitors and protease inhibitors in both treatment naïve and treatment-experienced children in different countries. Most of the patients with extensive triple-class drug resistant mutations were found to be considerably exposed to the three main classes of antiretroviral agents. Identification of genetic factors linked with susceptibility to perinatal transmission of HIV may be key in understanding the development of resistance due to waning antiviral effectiveness. Children who were less likely to achieve viral re-suppression were more likely to have resistance mutations. Newer drugs such as etravirine can be used as alternatives in case of resistance to efavirenz while newly developed diagnostic method such as next-generation sequencing is a platform for improving quality of detections especially minor variant drug resistance mutations.